American Foreign Policy towards Iraq, Iran and North Korea: American Hegemony and Neo-conservatism against the Axis of Evil - Seniwati, Seniwati (Jurusan Hubungan Internasional UNHAS, 2015)
This article analyzes the United States toward âaxis of evilâ countries, namely Iraq, Iran and North Korea. Since September 11, 2001, according to George Walker Bush, these countries are sponsor of terror that threat America or friendâs and alliesâ of America with weapons of mass destruction.